2015
DOI: 10.1088/1674-4926/36/3/033001
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformation from cubic ZnS to hexagonal ZnO by thermal annealing

Abstract: We have investigated the mechanism of phase transformation from ZnS to hexagonal ZnO by hightemperature thermal annealing. The ZnS thin films were grown on Si (001) substrate by thermal evaporation system using ZnS powder as source material. The grown films were annealed at different temperatures and characterized by X-ray diffraction (XRD), photoluminescence (PL), four-point probe, scanning electron microscope (SEM) and energy dispersive X-ray diffraction (EDX). The results demonstrated that as-deposited ZnS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Above ~1000 °C the stable phase is wurtzite, and below this temperature zincblende is stable, however, the mutual transformation is very slow, leaving wurtzite phase metastable at room temperature [19]. In the case of nanostructures, it has been reported that the transition to occur at a lower temperature [20,21]. Preliminary inspection of the XRD patterns revealed no diffraction peaks that could be attributed to other phases than the cubic ZnS-type (JCPDS Card no.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Above ~1000 °C the stable phase is wurtzite, and below this temperature zincblende is stable, however, the mutual transformation is very slow, leaving wurtzite phase metastable at room temperature [19]. In the case of nanostructures, it has been reported that the transition to occur at a lower temperature [20,21]. Preliminary inspection of the XRD patterns revealed no diffraction peaks that could be attributed to other phases than the cubic ZnS-type (JCPDS Card no.…”
Section: Resultsmentioning
confidence: 99%
“…The growth process can be explained two-step process: (i) formation of ZnO nanoparticles and (ii) axial growth of ZnO nanoparticles to form nanostructures. The detailed growth process is as follows during annealing process: in the first step, Zn-S bonds are broken and oxygen atoms from the atmosphere get high enough energy; in the second step, the oxygen atoms replaced the sulphur atom in the lattice and S to form Zn-O bonds [21]. As a wurtzite-structured metal oxide, ZnO belongs to the P63mc space group and has a highly anisotropic structure along the c-axis.…”
Section: Zno-based Zns-based a (å)mentioning
confidence: 99%